"Beyond the Boundary": A Countermovement to the Hollowing-out of Rural China. (July 2015) - Wu, Chongqing
Sun Village, located in a remote part of coastal Fujian, has a tradition of migratory economic activities supplementary to agriculture—a tradition that could be called tongxiang tongye (same hometown, same trade). On the basis of rural social networks, Sun villagers have established an industry processing golden and silver jewelry in cities throughout China. This phenomenon is a countermovement against the predominant trend of rural China's marginalization and "hollowing-out" relative to urban centers. This countermovement offers the possibility of reembedding economic activities within social relationships to create a "social economy." Jiewai ("Beyond the Boundary") is an alternative and pluralistic periphery that might undermine the center.